2014
DOI: 10.5194/bg-11-6791-2014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impediment of methane ebullition bubbles by seasonal lake ice

Abstract: Abstract. Microbial methane (CH 4 ) ebullition (bubbling) from anoxic lake sediments comprises a globally significant flux to the atmosphere, but ebullition bubbles in temperate and polar lakes can be trapped by winter ice cover and later released during spring thaw. This "ice-bubble storage" (IBS) constitutes a novel mode of CH 4 emission. Before bubbles are encapsulated by downward-growing ice, some of their CH 4 dissolves into the lake water, where it may be subject to oxidation. We present field characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
127
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(144 citation statements)
references
References 65 publications
(70 reference statements)
8
127
1
Order By: Relevance
“…Another reason is that yedoma lakes have a significantly higher ebullition year round (Walter et al, 2007;Sepulveda-Jauregui et al, 2015). Even during winter, Greene et al (2014) found that 80 % of CH 4 in ebullition bubbles trapped under the ice cover dissolves into the lake water column before being confined within the growing ice sheet, leading to elevated dissolved CH 4 beneath the ice.…”
Section: Geographic and Seasonal Variations In Physicochemical Paramementioning
confidence: 99%
See 1 more Smart Citation
“…Another reason is that yedoma lakes have a significantly higher ebullition year round (Walter et al, 2007;Sepulveda-Jauregui et al, 2015). Even during winter, Greene et al (2014) found that 80 % of CH 4 in ebullition bubbles trapped under the ice cover dissolves into the lake water column before being confined within the growing ice sheet, leading to elevated dissolved CH 4 beneath the ice.…”
Section: Geographic and Seasonal Variations In Physicochemical Paramementioning
confidence: 99%
“…This seasonal variation can be attributed to thick ice covering the lakes in winter. Ice cover impedes gas exchange between the water and the atmosphere, promoting CH 4 build-up in the water column (Phelps et al, 1998;Bastviken et al, 2004;Juutinen et al, 2009) and hindering O 2 transfer from the atmosphere, except in some locations where high-flux ebullition seeps allow gas exchange through local holes in lake ice (Greene et al, 2014). Ice and snow also reduce light penetration and oxygen production by photosynthesis beneath the ice (White et al, 2008;Clilverd et al, 2009).…”
Section: Geographic and Seasonal Variations In Physicochemical Paramementioning
confidence: 99%
“…Previous studies have documented significantly earlier ice breakup between the 1950s and 2000s for lakes in Canada (Duguay et al, 2006;Latifovic and Pouliot, 2007;Prowse et al, 2011) and decreasing ice cover duration of Eurasia lakes during the last few decades (Vuglinsky and Gronskaya, 2006;Karetnikov and Naumenko, 2008;Prowse et al, 2011). Shorter ice cover seasons may promote greater CH 4 emissions from northern lakes (Greene et al, 2014), which could reinforce further climate warming due to the role of CH 4 as a potent greenhouse gas. Despite a general tendency for later freezing and earlier breakup in the Northern Hemisphere , various tendencies including earlier ice formation and later ice breakup over specific lakes and time periods may exist.…”
Section: Introductionmentioning
confidence: 99%
“…1; Walter et al, 2006;Walter Anthony et al, 2012;Sepulveda-Jauregui et al, 2015). In spring, the break-up of the ice and mixing allows stored CH 4 to be oxidized or emitted from the system through diffusion or ebullition (Juutinen et al, 2009;López Bellido et al, 2009;Karlsson et al, 2013;Greene et al, 2014;Jammet et al, 2015). Emissions of stored CH 4 during overturn events accounts for up to 40 % of the total annual flux in lakes globally (Michmerhuizen et al, 1996;Juutinen et al, 2009;López Bellido et al, 2009;Encinas Fernandez et al, 2014;Jammet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Excess CH 4 that escapes MOx and reaches the upper mixed layer of the water column (epilimnion) is available for emission to the atmosphere by molecular diffusion under open-water conditions. Emission by ebullition and plants results in a direct flux of CH 4 to the atmosphere with limited oxidation in the water column (Keppler et al, 2006;Walter et al, 2006Walter et al, , 2007Nisbet et al, 2009;Wik et al, 2013;Greene et al, 2014).…”
Section: Introductionmentioning
confidence: 99%